(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The focus of this study is to examine the personal-organizational relationship in hotels This paper discussed the partnership of a strong employer brand with employees of an institution in our country and the advantages that this brand promised to employees with employees, Fit, employer branding, desirable employer, attractive employer, brand force employer, brand operation employer brand clarity, organization of brand. Material and mechanism collaborating, the advantage and advantages of employer branding Employer branding, employer branding and their management process, employer branding benefits